Bleeding in advanced CKD patients on antithrombotic medication – A critical appraisal. (March 2018) - Burlacu, Alexandru; Genovesi, Simonetta; Goldsmith, David; Rossignol, Patrick; Ortiz, Alberto; Kalra, Philip A.; Małyszko, Jolanta; Banach, Maciej; Kanbay, Mehmet; Covic, Adrian
Graphical abstract: HAS-BLED score calculation in advanced CKD patients with chronic atrial fibrillation and recent stent implantation. Abstract: Patients with advanced chronic kidney disease (CKD) are at an increased risk of bleeding, especially in the context of the complex therapeutic schemes of coronary artery disease (CAD) (from stable angina to acute coronary syndromes), atrial fibrillation or venous thromboembolism. The bleeding issue increases morbidity and mortality, a serious problem in daily medical practice. However, these patients are largely excluded from major randomized clinical trials, which results in the lack of medical evidence-based foundation for specific recommendations regarding antithrombotic treatment in a high bleeding risk setting. Within this framework, the clinician does not benefit from a clear set of algorithms and measures in the exploration and balancing of bleeding and thrombosis risks. We discuss a diversity of scenarios, encompassing all categories of advanced CKD patients with CAD or/and atrial fibrillation, and with various combinations of drugs, such as antiplatelet therapy or/and oral anticoagulation. Our review highlights the most recent research as well as existing gaps in the recommendations of European Society of Cardiology Guidelines. We evaluate the existence or lack of assessment tools for the bleeding risk, strength, reliability and usefulness of the bleeding risk scores. Also, we identify all the measures recommended after risk evaluation, including specific plans, dose adjustments and particular therapeutic approaches. Finally, we provide with suggestions for improving the management of this patient population.